2021
DOI: 10.3390/cells10081975
|View full text |Cite
|
Sign up to set email alerts
|

Alkylaminophenol and GPR17 Agonist for Glioblastoma Therapy: A Combinational Approach for Enhanced Cell Death Activity

Abstract: Drug resistance and tumor heterogeneity limits the therapeutic efficacy in treating glioblastoma, an aggressive infiltrative type of brain tumor. GBM cells develops resistance against chemotherapeutic agent, temozolomide (TMZ), which leads to the failure in treatment strategies. This enduring challenge of GBM drug resistance could be rational by combinatorial targeted therapy. Here, we evaluated the combinatorial effect of phenolic compound (2-(3,4-dihydroquinolin-1(2H)-yl)(p-tolyl)methyl)phenol (THTMP), GPR17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…By coupling it with TMZ, it is also possible to further hamper GBM growth. In 2021, Doan et al [ 207 ] explored the use of a combinatorial drug regimen including TMZ, GPR-17 agonist 2-({5-[3-(Morpholine-4-sulfonyl)phenyl]-4-[4-(trifluoromethoxy)phenyl]-4H-1,2,4-triazol-3-yl}sulfanyl)-N-[4-(propan-2-yl)phenyl]acetamide, and alkylaminophenol against GBM. They saw that the combination of alkylaminophenol and GPR-17 agonist reduced GBM migration, invasion, and proliferation.…”
Section: Personalized and Combination Therapiesmentioning
confidence: 99%
“…By coupling it with TMZ, it is also possible to further hamper GBM growth. In 2021, Doan et al [ 207 ] explored the use of a combinatorial drug regimen including TMZ, GPR-17 agonist 2-({5-[3-(Morpholine-4-sulfonyl)phenyl]-4-[4-(trifluoromethoxy)phenyl]-4H-1,2,4-triazol-3-yl}sulfanyl)-N-[4-(propan-2-yl)phenyl]acetamide, and alkylaminophenol against GBM. They saw that the combination of alkylaminophenol and GPR-17 agonist reduced GBM migration, invasion, and proliferation.…”
Section: Personalized and Combination Therapiesmentioning
confidence: 99%
“…glioblastoma cells with a combination of Mannich base 67 (R=CH 3 ) (Figure 8), G protein‐coupled receptor 17 (GPR17) agonist T0510.3657 (AKos GmbH, Stuttgart, Germany) and frontline drug temozolomide has shown that the best synergistic effects were obtained with a combination of aminoalkylphenol 67 (R=CH 3 ) and T0510.3657, which inhibited tumor cell proliferation, cell migration, invasion, colony‐forming ability and cell cycle progression in S phase better than any other combination, and also showed promising anti‐tumor efficacy in glioblastoma xenograft model by reducing the tumor volume [84] . In addition, phenolic Mannich base 68 (Figure 8) can act as an agonist activating endogenous GPR17 in LN229 and SNB19 glioblastoma multiforme cells, and it had a cytotoxic effect on these cells in a dose‐dependent manner with IC 50 =85 μM for SNB19 cells [85] .…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Derived F...mentioning
confidence: 99%